The experiment of eight million people: an investigation into the process of designing social policies in China - Riley, R (2017)
This project problematizes the general understanding of China's birth planning regime. By providing an analytical history of a two-child policy experiment, it moves beyond previous work to generate granular accounts of key policymaking decisions. A 'critical junctures' approach centred around what has been called the 'Experiment of Eight Million People' was leveraged to unlock this alternative chronology within China’s national fertility policy. The Experiment was a two-child pilot that governed select rural counties for more than thirty years, but it has not yet been systematically examined in the English-language literature. Tools from critical junctures theory, or the idea that explicating possible inflection points builds understanding of policy mechanisms, provide a framework to identify the times when the two-child design appeared most likely to be on the cusp of national expansion. Data from Chinese media, declassified internal government documents, secondary literature, and interviews with elite Chinese academics and policymakers are then leveraged to provide detailed descriptions of the events that predicated the policy outcomes at these points. This process yielded the first English account of the mechanisms that triggered China's change to a national two-child policy in 2015. Finally, results from this analysis were used to hypothesize about which political factors were most central in facilitating or obstructing changes in a Chinese social policy. Beyond Chinese birth planning specifically, the project has implications for the study of political factors enabling or constraining social policy change, welfare policy in East Asian and authoritarian states, and the degree to which population policies serve a social function.